EXPERIENCE OF THE VITAMN AND MINERAL COMPLEXES IN CHILDREN - I.A. Gromov; E.A. Galeeva; L.S. Namazova-Baranova; R.М. Torshkhoeva; L.M. Krasnykh (Union of pediatricians of Russia, 2009)
High spread of the subnormal vitamin provision of the children population leads to the increased frequency of the hypovitaminosis development. Solution to the problem is to compensate the deficiency of vitamins and microelements by prescribing corresponding combined pharmacological means. The authors show that vitamins and minerals may affect the activity and metabolism of one another by performing their specific functions. The article provides for the findings of the research, in which authors examined the interaction between each single component of the vitamin and mineral complex in the event of their simultaneously absorption.Key words: vitamins, minerals, hypovitaminosis, treatment, children.